Theoretical models of learning and literacy development - Ortlieb, Evan.; Cheek, Earl H. (Bingley, U.K. : Emerald, 2014)
This book advances theoretical knowledge through rich description of cognitive and social elements of the teaching and learning processes of literacy formation. This text offers ten theories that describe how students learn in the 21st century and how to improve curriculum and instruction towards meeting the current needs of students today.
Attraction theory / Evan Ortlieb -- Spacing theory / Evan Ortlieb -- Backwards sequencing theory / Evan Ortlieb -- Read fast, read slow theory / Evan Ortlieb -- Experiential learning theory / Evan Ortlieb -- Extending theory / Evan Ortlieb -- Language creation / Evan Ortlieb -- Capital investment theory / Evan Ortlieb -- Learn over theory / Evan Ortlieb -- E-reading theory / Evan Ortlieb.
Print version record
Keywords: Education -- Research; Education; Reading